Georgia : a political history since independence - Jones, Stephen Francis (I.B. Tauris, 2013)
"Georgia emerged from the fall of the Soviet empire in 1991 with the promise of swift economic and democratic reform. But that promise remains unfulfilled. Economic collapse, secessionist challenges, civil war and the failure to escape the legacy of Soviet rule - culminating in the 2008 war with Russia - characterise a two-decade struggle to establish democratic institutions and consolidate statehood. Here, Stephen Jones critically analyses Georgia's recent political and economic development, illustrating what its 'transition' has meant, not just for the state, but for its citizens as well. An authoritative and commanding exploration of Georgia since independence, this is essential for those interested in the post-Soviet world."--Bloomsbury publishing.